Multimodal therapy for rigid, persistent avoidant/restrictive food intake disorder (ARFID) since infancy: A case report. (April 2021) - Dolman, Lena; Thornley, Sarah; Doxtdator, Kyrsten; Leclerc, Anick; Findlay, Sheri; Grant, Christina; Breakey, Vicky R; Couturier, Jennifer
Avoidant/restrictive food intake disorder (ARFID) is a feeding and eating disorder that results in nutritional inadequacies, weight loss, and/or dependence on enteral feeds, and for which three clinical subtypes have been described. We present a unique case of an 11-year-old boy with rigid ARFID since infancy and features of all three ARFID subtypes. The patient presented with a life-long history of sensory aversion, limited intake and phobia of vomiting resulting in restriction to a single food item (yogurt) for more than 5 years. He presented with severe iron-deficiency anaemia, and deficiencies of vitamins A, C, D, E and zinc. We employed a multimodal therapeutic approach that incorporated elements of cognitive-behavioural therapy (CBT), family-based therapy (FBT) and pharmacological management with an antidepressant medication (sertraline) and an atypical antipsychotic agent (olanzapine). Over the course of a 7-week admission, our approach assisted the patient in successful weight restoration and incorporation of at least three new food items into his daily diet. While there are currently no first-line recommendations for ARFID management, our study lends support to the efficacy of CBT, FBT and pharmacological management for ARFID patients, including complex cases with multiple subtype features. Further research is needed to strengthen ARFID clinical guidelines.